EFFECT OF PRIVACY SECURITY, WEBSITE CONTENT, CUSTOMER SERVICE AND ATMOSPHERIC ON E-SHOPPING INTENTION - Mirna Zahara; Rahmaniar; Jullimursyida; Munandar (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2024)
This research aims to analyze the influence of Privacy Security, Website Content, Customer Service and Atmosphere on E-Shopping Intention among students at the Faculty of Economics and Business, Malikussaleh University. Data for this research was collected through a survey method using a questionnaire as a data collection instrument. The respondents used in this research were 112 students from the Faculty of Economics and Business, Malikussaleh University. This research uses a quantitative approach with multiple linear regression analysis using SPSS (Statistical Package for the Social Sciences) software. The research results show that privacy/security influences e-shopping intention, website content influences e-shopping intention, customer service influences e-shopping intention, atmospheric influences e-shopping intention and simultaneously privacy/security, website content, customer service and atmosphere influence e-shopping intention.